Effect of intervention programs to promote fundamental motor skills among typically developing children: a systematic review and meta-analysis - Zhang, Dong; Soh, Kim Geok; Chan, Yoke Mun; Zaremohzzabieh, Zeinab (Elsevier, 2024)
Background: Proficiency in fundamental motor skills (FMS) is associated with children's overall development and long-term physical literacy. However, FMS is not acquired naturally, but needs to be trained. Objective: This study aims to evaluate and provide up-to-date evidence on the effectiveness of intervention programs focused on promoting FMS among typically developing children between 2010 and 2022. Methods: Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a search was conducted in four databases (PubMed, Scopus, Web of Science, and SPORT Discus) from January 2010 to December 2022. Studies included any interventions in preschools and primary schools that aimed to improve fundamental motor skills in typically developing children aged 3 to 12, and reported fundamental motor skills outcomes and statistics. Results: Thirty-six articles (21 randomized controlled trials, 11 pre-post trials, and four quasi-experimental trials) satisfied all inclusion and exclusion criteria. Outcomes were primarily demonstrated in composite fundamental motor skills (n = 32) and its three primary parts: locomotor skills (n = 26), object control skills (n = 26), and balance skills (n = 4). A meta-analysis was conducted on 16 of these publications, revealing significant intervention effects for overall FMS proficiency (Std diff in means = 0.928, 95 % confidence interval 0.744–1.112, P = 0.001), locomotor skills (Std diff in means = 0.636, 95 % confidence interval 0.508–0.765, P = 0.001) and object control skills (Std diff in means = 0.871, 95 % confidence interval 0.660–1.081, P = 0.001). Discussion and Conclusions: The results indicate that implementing FMS development intervention programs in preschools and primary schools can be effective in promoting typically developing children's fundamental motor skills. The interventions on object control skills had a more significant effect size than locomotor skills. However, existing evidence cannot conclude which types of interventions are most effective.